A Fluorescence Probe for Metal Ions Based on Black Phosphorus Quantum Dots. Issue 7 (11th February 2020) - Xu, Zhenyu; Hu, Liang; Yuan, Jun; Zhang, Yiyue; Guo, Yujie; Jin, Zhengyuan; Long, Fangchao; Long, Yaojia; Liang, Huawei; Ruan, Shuangchen; Zeng, Yu‐Jia
Abstract: Fluorescence method for detecting metal ions has advantages of fast detection speed, simple operation, and low price over the conventional methods. Black phosphorus quantum dots (BP QDs) have high photoluminescence quantum yield and modifiable surface, which have great potential in the field of fluorescent probes. In this study, high quality BP QDs are prepared by pyrolysis method and are first time used as trace metal ion probes in both organic solutions and aqueous solutions. The detection limits of Hg 2+ and Cu 2+ in the aqueous solution are 5.3 × 10 −9 m and 1.6 × 10 −6 m, respectively. In addition, the detection limits of Cu 2+ in the organic solution are 16 × 10 −6 m . The fluorescence quenching mechanism based on the calculation of the electronic structure and adsorption energy of BP QDs after adsorption of metal ions is further explained. The results provide a new promising fluorescence probe for trace metal ions without the help of organic molecules. Abstract : Black phosphorus quantum dots (BP QDs) with green fluorescence emission are prepared, which can directly detect trace Hg 2+ and Cu 2+ ions without the help of organic molecules in both aqueous and organic phases. The fluorescence quenching mechanism of BP QDs after adsorption of metal ions is further explained through the calculation of the electronic structure and adsorption energy.